Effects of electron-beam irradiation on fatty acids profile of Agaricus bisporus Portobello - Cardoso, Rossana V.C. (2018)
The knowledge about the composition of mushrooms used in food has been increasing in recent years, but their high perishability leads to immediate quality losses after harvesting, which is a drawback for the distribution and marketing of the fresh product. Furthermore, mushrooms have a great popularity all over the world, but data on alternative technologies to increase their shelf life of mushrooms are insufficient. Irradiation is a technique recognized as safe and effective for conservation, and is widely used to extend the shelf life of raw foods. This work evaluates the effects of storage time (ST) (0, 4 and 8 days) and electron-beam (EB) irradiation on fatty acids profile (characterized by GC-FID) of fresh samples of Agaricus bisporus Portobello. The irradiation was performed with a 10 MeV energy irradiator at doses of 1, 2 and 5 kGy. ST and EB irradiation had a cooperative effect (i.e., the interaction among factors was significant, p-value < 0.05) over fatty acids profile. Comparing each factor individually, EB had a more noticeable effect than ST; in fact, the differences among fatty acids percentages for each EB dose were significant in all cases except C18:1n9c (oleic acid), while ST had no significant effects on C12:0, C13:0, C15:0, C18:1n9c, C18:2n6t, C18:3n3, C21:0 and MUFA. Linoleic acid (C18:2n6c) was the most abundant acid (≈78%), presenting slightly higher percentages in mushrooms irradiated with 1 kGy, showing in turn a minor decrease after 8 days of storage. Palmitic acid (≈8%) and stearic acid (≈4%), were the other main fatty acids in A. bisporus. Despite the detected differences, mushrooms presented a similar profile either within different EB doses, as well as along ST. Nevertheless, the 4-days storage maintains the fatty acids profile in higher extent than the 8-days storage; likewise, the best EB dose resulted to be 1 kGy.